2007
DOI: 10.1152/ajpregu.00113.2007
|View full text |Cite
|
Sign up to set email alerts
|

Liver injury after an aggressive encounter in male mice

Abstract: Sánchez O, Viladrich M, Ramírez I, Soley M. Liver injury after an aggressive encounter in male mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 62 publications
4
24
0
2
Order By: Relevance
“…We can therefore not rule out the possibility that anticipatory appraisal of the CAPS interview as overly threatening might have elicited an increase in liver enzymes in relation to PTSD severity. Our finding of PTSD predicting circulating levels of hepatic enzymes are in accordance with considerably consistent literature about psychological stress causing liver injury and an increase in hepatic enzymes in rodents [4][5][6][7]. Our data also concur with cross-sectional associations between chronic life stress and the degree of chronic hepatitis and ALT levels in humans [9,10].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We can therefore not rule out the possibility that anticipatory appraisal of the CAPS interview as overly threatening might have elicited an increase in liver enzymes in relation to PTSD severity. Our finding of PTSD predicting circulating levels of hepatic enzymes are in accordance with considerably consistent literature about psychological stress causing liver injury and an increase in hepatic enzymes in rodents [4][5][6][7]. Our data also concur with cross-sectional associations between chronic life stress and the degree of chronic hepatitis and ALT levels in humans [9,10].…”
Section: Discussionsupporting
confidence: 92%
“…However, PTSD patients have a greater degree of sympathetic nervous system activation [11]. In rats, transaminases were significantly increased 3 h after acute psychological stress [4]. We can therefore not rule out the possibility that anticipatory appraisal of the CAPS interview as overly threatening might have elicited an increase in liver enzymes in relation to PTSD severity.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The results of these studies showed that the experimental exposure of guinea pigs to psychological stress had a negative impact on the liver and the effect was even more pronounced in animals with pre-existing liver or cardiovascular diseases. Sanchez et al in 2007 described the development, in lab male mice, of an increase in plasma concentrations of ALT and AST after three hours of exposure to severe psychological stress and the occurrence of necrotic lesions of the parenchyma with damages of liver hepatocytes after 8 hours of exposure (66). Similar results were obtained by other Authors, such as Salas et al who described through electron microscopy the development of liver autophagic reactions compatible with liver injury in guinea pigs after 2 days of acute exposure to different varieties of psychological stressor (67).…”
Section: Comparing the Results Of The Questionnaire Hse And Liver Parmentioning
confidence: 99%
“…These glands release EGF into the saliva and blood plasma upon acute α 1 -adrenergic stimulation [6]. Accordingly, several stressors increase the EGF concentration in the plasma of male mice [13, 38,47,48].…”
Section: Introductionmentioning
confidence: 99%